2013
DOI: 10.5194/hess-17-913-2013
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of insurance damage claims related to rainfall extremes

Abstract: Abstract. In this paper, a database of water-related insurance damage claims related to private properties and content was analysed. The aim was to investigate whether the probability of occurrence of rainfall-related damage was associated with the intensity of rainfall. Rainfall data were used for the period of [2003][2004][2005][2006][2007][2008][2009] in the Netherlands based on a network of 33 automatic rain gauges operated by the Royal Netherlands Meteorological Institute. Insurance damage data were aggre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 22 publications
5
62
0
Order By: Relevance
“…Therefore, we have been able to confirm that 30 min rainfall is a better predictor of the probability of large damages than daily rainfall in urban areas, and this result confirms previous studies such as that of Torgersen et al (2015), who found a significant relationship between insurance data and short-lasting rainfall when studying urban floods in Norway. In addition, Spekkers et al (2013) showed that high claim numbers associated with private property and content damage were significantly related to maximum rainfall intensity, based on a logistic regression, with rainfall intensity for 10 min to 4 h time windows.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we have been able to confirm that 30 min rainfall is a better predictor of the probability of large damages than daily rainfall in urban areas, and this result confirms previous studies such as that of Torgersen et al (2015), who found a significant relationship between insurance data and short-lasting rainfall when studying urban floods in Norway. In addition, Spekkers et al (2013) showed that high claim numbers associated with private property and content damage were significantly related to maximum rainfall intensity, based on a logistic regression, with rainfall intensity for 10 min to 4 h time windows.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent works have used this kind of data to explore the causes and impacts of floods. For instance, in several European regions researchers have noted that precipitation has a significant influence on flood insurance data (see, for instance, Spekkers et al, 2013Spekkers et al, , 2015, for the Netherlands; Zhou et al, 2013, for Denmark;Sampson et al, 2014, for Ireland;Moncoulon et al, 2014, for France;Torgersen et al, 2015, for Norway). These data are very valuable for establishing causal relationships between the costs of flood damage and precipitation extremes, for developing risk maps and to use as a validation tool for damage models (Zhou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studying the spatial distribution of possible explanatory variables may help to explain how a heavy rainfall event triggers occurrence of flooding impacts in a city. Recent works have analyzed whether occurrence of citizens' complaints and insurance claim reports on rainfall-related incidents could be explained by variability in urban topography (Gaitan et al, 2015) and rainfall intensity (Spekkers et al, 2013). Response and explaining variables in those studies were selected apriori.…”
Section: Introductionmentioning
confidence: 99%
“…Jacobs, 2012), are examples of such measures. However, their effectiveness depends on the available knowledge of the mechanisms leading to damage after heavy rains, which are still not completely understood (Gaitan et al, 2015;Spekkers et al, 2013Spekkers et al, , 2014ten Veldhuis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Parker, Priest, & McCarthy, 2011;Spekkers, Kok, Clemens, & ten Veldhuis, 2013). Understanding of historic urban development in relation to this type of flooding could contribute to our understanding of these mechanisms.…”
Section: Introductionmentioning
confidence: 99%